The Potential of MicroRNAs in the Context of Sarcopenic Obesity - Chobolová, N; Švagera, Z; Stejskal, D; Bužga, M (Physiological research, 2025)
Sarcopenic obesity (SO) is a complex pathological condition characterized by the simultaneous presence of excessive adipose tissue and the loss of muscle mass and strength. This combination leads to an increased risk of metabolic, cardiovascular, and functional complications. In recent years, there has been growing interest in the use of microRNAs (miRNA) as biomarkers capable of detecting early changes in body composition and predicting the progression of SO. MiRNAs are small noncoding RNA molecules that play a key role in regulating gene expression and cellular pathways related to inflammation, metabolism, and muscle trophism. This article summarizes current knowledge about miRNAs expression in patients with sarcopenic obesity, their regulatory functions, and their potential use in diagnostics and therapy. Key words microRNA " Sarcopenic obesity " miRNA " Biomarkers " Muscle atrophy " Inflammation.
Keywords: Biomarkers; biologické markery; mikro RNA; obezita; MicroRNAs; zvířata; kosterní svaly; lidé; sarkopenie; Sarcopenia; Animals; Humans; Muscle, Skeletal; Obesity